From legislative simulation to early civic engagement: Nurturing young minds for social change - The brazilian case - Pires, Sergio Fernandes Senna (Seven Editora, 2024)
This study investigates how legislative simulation programs since 2003 have played a crucial role in imparting democratic values and socio-emotional education to children and adolescents. Since its inception in 2003, the program has undergone several enhancements to better foster citizenship and provide practical legislative experiences. The program's engaging and educational activities aim to develop key psychological skills such as autonomy, self-reflection, distancing, and self-determination, laying the foundation for democratic engagement and coexistence. Moreover, the study emphasizes how digital activities significantly enhance the internalization of democratic values and socio-emotional skills among participants. While individual factors play a role, the predominant influence stems from societal practices and values. This innovative approach not only educates young citizens about legislative processes, but also instills in them the principles of democracy and active participation. In conclusion, the study underscores the program's vital contribution to nurturing informed, reflective, and participatory individuals—key to building a just and democratic society. DOI:https://doi.org/10.56238/sevened2024.007-097